Evaluation of beam delivery and ripple filter design for non-isocentric proton and carbon ion therapy. (29th September 2015) - Grevillot, L; Stock, M; Vatnitsky, S
Abstract: This study aims at selecting and evaluating a ripple filter design compatible with non-isocentric proton and carbon ion scanning beam treatment delivery for a compact nozzle. The use of non-isocentric treatments when the patient is shifted as close as possible towards the nozzle exit allows for a reduction in the air gap and thus an improvement in the quality of scanning proton beam treatment delivery. Reducing the air gap is less important for scanning carbon ions, but ripple filters are still necessary for scanning carbon ion beams to reduce the number of energy steps required to deliver homogeneous SOBP. The proper selection of ripple filters also allows a reduction in the possible transverse and depth-dose inhomogeneities that could appear in non-isocentric conditions in particular. A thorough review of existing ripple filter designs over the past 16 years is performed and a design for non-isocentric treatment delivery is presented. A unique ripple filter quality index (QIRiFi ) independent of the particle type and energy and representative of the ratio between energy modulation and induced scattering is proposed. The Bragg peak width evaluated at the 80% dose level (BPW80 ) is proposed to relate the energy modulation of the delivered Bragg peaks and the energy layer step size allowing the production of homogeneous SOBP. Gate/Geant4 Monte Carlo simulations have been validated for carbon ion and ripple filter simulations based on measurements performed at CNAO and subsequently used for a detailed analysis of the proposed ripple filter design. A combination of two ripple filters in a series has been validated for non-isocentric delivery and did not show significant transverse and depth-dose inhomogeneities. Non-isocentric conditions allow a significant reduction in the spot size at the patient entrance (up to 350% and 200% for protons and carbon ions with range shifter, respectively), and therefore in the lateral penumbra in the patients.